Inhibitory effect of deferoxamine on Paracoccidioides brasiliensis survival in human monocytes: Reversal by holotransferrin not by apotransferrin - Dias-Melicio, Luciane Alarcão [UNESP]; Calvi, Sueli Aparecida [UNESP]; Peraçoli, Maria Terezinha Serrão [UNESP]; Soares, Ângela Maria Victoriano de Campos [UNESP] (My University, 2005)
The mechanisms used by Paracoccidioides brasiliensis to survive into phagocytic cells are not clear. Cellular iron metabolism is of critical importance to the growth of several intracellular pathogens whose capacity to multiply in mononuclear phagocytes is dependent on the availability of intracellular iron. Thus, the objective of this paper was to investigate the role of intracellular iron in regulating the capacity of P. brasiliensis yeast cells to survive within human monocytes. Treatment of monocytes with deferoxamine, an iron chelator, suppressed the survival of yeasts in a concentration-dependent manner. The effect of deferoxamine was reversed by iron-saturated transferrin (holotransferrin) but not by nonsaturated transferrin (apotransferrin). These results strongly suggest that P. brasiliensis survival in human monocytes is iron dependent.
Keywords: Deferoxamine; Iron; Monocytes; Paracoccidioides brasiliensis; apotransferrin; deferoxamine; holotransferrin; iron chelate; unclassified drug; cell culture; cell level; controlled study; culture medium; fungus growth; human; human cell; iron metabolism; monocyte; nonhuman; phagocyte; survival; Apoproteins; Humans; Paracoccidioides; Siderophores; Transferrin